Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/polym13244293
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Strength of Plastic Parts Improved with Selective Induction Heating

Abstract: The use of selective induction heating of molding surfaces allows for better filling of molding cavities and has a positive effect on the properties of molded products. This is particularly important in the production of parts that include flexible hinges, which are thin plastic layers connecting two or more parts of the product. By using hinges, it is possible to expand the use of injection molding products and their capabilities. They are widely used in the production of parts for the electrical engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…These issues can be addressed by directly heating the cavity surface. There are several methods that can support a high heating rate and good predictability without heating the entire cavity volume, for example, induction heating [ 22 , 23 , 24 , 25 ], high-frequency proximity heating [ 26 , 27 ], and gas-assisted mold temperature control (GMTC) [ 28 , 29 , 30 , 31 , 32 ]. The induction heating method has a very fast heating rate, which is a great advantage.…”
Section: Introductionmentioning
confidence: 99%
“…These issues can be addressed by directly heating the cavity surface. There are several methods that can support a high heating rate and good predictability without heating the entire cavity volume, for example, induction heating [ 22 , 23 , 24 , 25 ], high-frequency proximity heating [ 26 , 27 ], and gas-assisted mold temperature control (GMTC) [ 28 , 29 , 30 , 31 , 32 ]. The induction heating method has a very fast heating rate, which is a great advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, increasing the mold temperature will prolong the molding time required for the plastic part (the plastic part must be cooled to the ejection temperature in the mold before the mold can be opened), resulting in unnecessary costs. Poszwa et al [ 32 ] investigated the injection molded flexible hinge parts manufactured with selective induction heating to improve their properties. The linear relation between the number of cycles the hinges can withstand, mold temperature, and injection time was identified.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, parts obtained with high cavity temperature show longer durability than parts obtained by conventional processes. [2,3] Lucchetta et al [4] demonstrated that the appearance of acrylonitrile butadiene styrene parts can be significantly improved using high mold temperature during the process. Liu et al [5] proved the improvement of tensile strength in the glass-fiber filled polypropylene specimens.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] However, most of the proposed methods show slow heating and cooling rates (10 °C s −1 ), cause excessively long processing time. Induction heating, infrared heating, and high proximity heating [2,9,10] can realize cavity heating with a rate of 50 °C s −1 . [2,11] Although fast, those methods require high investment costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation